2015
DOI: 10.4081/monaldi.2012.141
|View full text |Cite
|
Sign up to set email alerts
|

Psychological profiles derived by cluster analysis of Minnesota Multiphasic Personality Inventory and long term clinical outcome after coronary artery by pass grafting

Abstract: After CABG, the interpretation of MMPI-2 by cluster analysis is useful for the psychological and personological diagnosis to direct psychological assistance. Conversely, results from cluster analysis of MMPI-2 do not seem helpful to the clinician to predict long term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Of the seven excluded studies, two of three studies in patients with HF showed a significant association between type D personality and mortality using the two-group method (77)(78)(79). The four remaining studies focused on patients with CAD, three of which used the two-group method to show that type D personality was associated with MACE (80)(81)(82), whereas one study indicated that a cluster with patients with CAD scoring high on type D personality had an increased risk of all-cause mortality during follow-up than other patient clusters (83). None of these seven studies used the continuous method to estimate type D effects, leaving it unclear whether type D personality was driving these effects.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Of the seven excluded studies, two of three studies in patients with HF showed a significant association between type D personality and mortality using the two-group method (77)(78)(79). The four remaining studies focused on patients with CAD, three of which used the two-group method to show that type D personality was associated with MACE (80)(81)(82), whereas one study indicated that a cluster with patients with CAD scoring high on type D personality had an increased risk of all-cause mortality during follow-up than other patient clusters (83). None of these seven studies used the continuous method to estimate type D effects, leaving it unclear whether type D personality was driving these effects.…”
Section: Strengths and Limitationsmentioning
confidence: 99%